Measurement of the branching fraction of the decay B-s(0) -> (KSKS0)-K-0 - Aaij,R; Beteta,CA; Adeva,B; Adinolfi,M; Aidala,CA; Ajaltouni,Z; Akar,S; Albicocco,P; Albrecht,J; Alessio,F; Alexander,M; Albero,AA; et al. (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2020)
A measurement of the branching fraction of the decay B0s→K0SK0S is performed using proton–proton collision data corresponding to an integrated luminosity of 5  fb−1 collected by the LHCb experiment between 2011 and 2016. The branching fraction is determined to be B(B0s→K0SK0S)=[8.3±1.6(stat)±0.9(syst)±0.8(norm)±0.3(fs/fd)]×10−6, where the first uncertainty is statistical, the second is systematic, and the third and fourth are due to uncertainties on the branching fraction of the normalization mode B0→K0S and the ratio of hadronization fractions fs/fd. This is the most precise measurement of this branching fraction to date. Furthermore, a measurement of the branching fraction of the decay B0→K0SK0S is performed relative to that of the B0s→K0SK0S channel, and is found to be B(B0→K0SK0S)B(B0s→K0SK0S)=[7.5±3.1(stat)±0.5(syst)±0.3(fs/fd)]×10−2.